PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATA PELAJARAN IPAS DI KELAS IV SD BERBASIS KEBUTUHAN PESERTA DIDIK - M. Anggrayni; Riyadi Saputra; Yusrida (STKIP Subang, 2023)
This research is motivated by the lack of development of LKPD, the LKPD used is a school package book and is not in accordance with the independent curriculum and it must be adjusted to the curriculum and the needs of students, so that it has an impact on students such as being less active in ongoing learning activities, the learning process seems to watch and learning success becomes low. Efforts to overcome these problems require teaching materials in the form of LKPD based on the needs of students so that so that education students can be more active, independent and can achieve the learning goals that have been applied. This research aims to produce teaching material products in the form of LKPD based on student needs. this type of research is Research and Development development. This development model is the ADDIE development model. In the development of ADDIE there are five stages of procedures, namely Analysis, Design, Development, Implementation and Evaluation. Based on the validity test results of three expert validators have a content validation score of 77.7%, graphic aspect 76.6%, and language aspect 93%. Based on these three aspects of the assessment, the average percentage is 81% with a very valid category. The results of the practicality test from the assessment of grade IV teacher responses were obtained 87.5% and the assessment of students was obtained 85.21%. So that a percentage of 85% is obtained with a very practical category. Based on these results, it can be concluded that the LKPD based on the needs of Class IV Elementary IPAS Subject Students developed can be declared valid, practical and effective.